Hadith #2346 - Sunan Abi Dawud - Abu 'Uthman al-Nahdi عبد الرحمن بن مل - أبو عثمان النهدي; ibn Mas'ud; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
The adhan (call to prayer) of Bilal should not prevent you from taking a meal shortly before dawn, not does the whiteness of horizon (before dawn) in this way (vertically) until it spreads out horizontally.
Grade: Sahih

Hadith #3124 - Sunan Abi Dawud - Abu 'Uthman al-Nahdi عبد الرحمن بن مل - أبو عثمان النهدي; Asim al-Ahwal عاصم الأحول; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Usamah ibn Zayd (Sunan Abi Dawud)
The Prophet (ﷺ) came upon a woman who was weeping for her child. He said to her: Fear Allah and have patience. She said: What have you to do with my calamity ? She was then told that he was the Prophet (ﷺ). She, therefore, came to him. She did not find doorkeepers at his gate. She said: I did not recognize you, Messenger of Allah. He said: Endurance is shown only at a first blow.
Grade: Sahih

Hadith #3270 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Abdur Rahman bin Abi Bakr; Abu 'Uthman al-Nahdi عبد الرحمن بن مل - أبو عثمان النهدي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Sa'id bin Iyas al-Jariri سعيد بن إياس الجريري; Salm bin Nwh bin Aby سالم بن نوح بن أبي (Sunan Abi Dawud)
Some guests visited us, and Abu Bakr was conversing with the Messenger of Allah (ﷺ) at night. He (Abu Bakr) said: I will not return to you until you are free from their entertainment and serving them food. So he brought them food, but they said: We shall not eat it until Abu Bakr comes (back). Abu Bakr then came and asked: What did your guest do? Are you free from their entertainment ? They said: No. I said: I brought them food, but they refused and said: We swear by Allah, we shall not take i
Grade: Sahih

Hadith #3686 - Sunan Abi Dawud - Abu 'Uthman al-Nahdi عبد الرحمن بن مل - أبو عثمان النهدي; Aisha bint Abi Bakr; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; Mahdi bin Maymun al-Azdi مهدي بن ميمون الأزدي المعولي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade every intoxicant and everything which produces languidness.
Grade: Da'if

Hadith #3812 - Sunan Abi Dawud - Abu 'Uthman al-Nahdi عبد الرحمن بن مل - أبو عثمان النهدي; Salman Farsi; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan Abi Dawud)
I heard Ibn Abi Awfa say when I asked him about (eating) locusts: I went on six or seven expeditions along with the Messenger of Allah (ﷺ) and we ate them (locusts) along with him.
Grade: Sahih

Hadith #3813 - Sunan Abi Dawud - Abu 'Uthman al-Nahdi عبد الرحمن بن مل - أبو عثمان النهدي; Ali bin al-Madini علي بن المديني; Nasr bin 'Ali bin Nasr bin 'Ali; Salman Farsi; Zakaria bin Yahya bin Amarh زكريا بن يحيى بن عمارة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) was asked about (eating) locusts. He replied: They are the most numerous of Allah’s hosts. I neither eat them nor declare them unlawful.
Grade: Da'if

Hadith #4041 - Sunan Abi Dawud - Abu 'Uthman al-Nahdi عبد الرحمن بن مل - أبو عثمان النهدي; Asim al-Ahwal عاصم الأحول; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
He said: A robe of silk brocade. He then sent him a Jubbah of brocade and said: You may sell it and fulfill your need.
Grade: Sahih

Hadith #5111 - Sunan Abi Dawud - Abu 'Uthman al-Nahdi عبد الرحمن بن مل - أبو عثمان النهدي; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Asim al-Ahwal عاصم الأحول; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
Have you experienced that? They replied: yes. He said : that is clear faith.
Grade: Sahih